2011
DOI: 10.1158/0008-5472.can-11-1285
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 Agonists Oppositely Modulate DNA Repair Genes in Tumor versus Immune Cells and Enhance Chemotherapy Effects

Abstract: Synthetic oligodeoxynucleotides expressing CpG motifs (CpG-ODN) are a Toll-like receptor 9 (TLR9) agonist that can enhance the antitumor activity of DNA-damaging chemotherapy and radiation therapy in preclinical mouse models. We hypothesized that the success of these combinations is related to the ability of CpG-ODN to modulate genes involved in DNA repair. We conducted an in silico analysis of genes implicated in DNA repair in data sets obtained from murine colon carcinoma cells in mice injected intratumorall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 45 publications
2
52
0
Order By: Relevance
“…[6][7][8][9] Our results indicate that this is not true for tumors growing in the lung, where both tumor immunogenicity and the tumor-induced immunosuppressive environment are critical factors in the success of CpG therapy. Thus, different administration routes might be required for different tumors.…”
Section: Tumor Immunologymentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9] Our results indicate that this is not true for tumors growing in the lung, where both tumor immunogenicity and the tumor-induced immunosuppressive environment are critical factors in the success of CpG therapy. Thus, different administration routes might be required for different tumors.…”
Section: Tumor Immunologymentioning
confidence: 99%
“…The anti-tumor effect of CpG has been optimized by direct injection into the tumor to enable increased local concentrations in the tumor microenvironment and to ensure effective local activation of both innate and adaptive immune responses. [6][7][8][9] Thus, local instead of systemic administration of the TLR9 agonist might represent an option to improve the efficacy of CpG as adjuvant in protecting against lung cancer or in treating and/or preventing lung metastases derived from different primary tumors. Bronchial and bronchoalveolar tumors are accessible via the endobronchial space.…”
mentioning
confidence: 99%
“…Previous studies have showed that CpG-ODN can mediate anti-tumor effects on cancer cells due to its direct or indirect effects by inducing release of cytokines, and enhancing immune response [11]. Meanwhile, recent studies suggested that CpG-ODN may be considered as a potential chemosensitizer with weak side effects, such CpG-ODN 1826 [12,13] Clinical studies have also documented that CpG-ODN in combination with chemotherapy cannot only increase the treatment benefit of patients ,but also make patients with well tolerated [14,15]. Although a previous study had demonstrated the benefits of CpG-ODN for HCC treatment [16], the direct cytotoxicity of CpG-ODN against HCC cells and the potential mechanism are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…That upon detecting the presence of an infectious agent via endosomal TLRs, immune cells might up-regulate DNA repair genes to decrease their susceptibility to possible pro apoptotic signals during infections (Sommariva et al, 2011). Also TLR-9 pathway was demonstrated to modulate the expression of DNA repair genes.…”
Section: Group I (Treated With Cpg Odn)mentioning
confidence: 99%
“…Because chemotherapy is known to be immunosuppressive, it is advisable to combine chemotherapy with TLR9 stimulation during treatment (Vollmer and Krieg, 2009). Particular clinical interest now revolves around TLR9, which is expressed not only on cells of the immune system but also on endothelial cells, fibroblasts and epithelial cells and which recognizes bacterial and viral DNA with unmethylated CpG motifs (Sommariva et al, 2011). Local, but not systemic and daily, but not weekly, stimulation of immune effectors cells by CpG-ODN targeted immunotherapy modulates genes involved in DNA repair, increasing their expression in TLR9-expressing immune cells but down regulating their expression in tumor cells and thereby increasing sensitivity to DNA-damaging chemotherapeutic agents (De Cesare et al, 2010).…”
Section: Introductionmentioning
confidence: 99%